2015
DOI: 10.1016/j.pubrev.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Le tweet stratégique: Use of Twitter as a PR tool by French politicians

Abstract: Edited By Dejan Verčič, Ana Tkalac Verčič, Krishnamurthy Sriramesh and Jon WhiteNational audienceThis study, adopting a qualitative approach to political communication, looks in depth at the way Twitter is used as a PR tool by five French politicians. It suggests that the microblogging service plays a specific role in allowing them to monitor public opinion and current affairs, to interact with voters, journalists, stakeholders and other politicians and to disseminate information. The way politicians use Twitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 9 publications
2
18
0
3
Order By: Relevance
“…Tromble, 2016a). Like in our study, these researchers also note that most interaction takes place between MPs and accounts that do not belong to lay citizens (Ahmed et al, 2016;Frame & Brachotte, 2015;Tromble, 2016b; but see: Graham, Jackson & Broersma, 2016, p. 775). 34 Our study thus confirms and updates existing insights and additionally highlights that the position an MP has within a party seems to matter as well: The more an MP is a backbencher, the more she is likely to interaction with accounts of lay citizens.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Tromble, 2016a). Like in our study, these researchers also note that most interaction takes place between MPs and accounts that do not belong to lay citizens (Ahmed et al, 2016;Frame & Brachotte, 2015;Tromble, 2016b; but see: Graham, Jackson & Broersma, 2016, p. 775). 34 Our study thus confirms and updates existing insights and additionally highlights that the position an MP has within a party seems to matter as well: The more an MP is a backbencher, the more she is likely to interaction with accounts of lay citizens.…”
Section: Resultssupporting
confidence: 75%
“…Like in our study, they find that MPs mainly, though not exclusively, use Twitter as a "broadcasting tool" (Ahmed, Jaidka, & Cho, 2016, p. 1079Arnaboldi, Passarella, Conti, & Dunbar, 2017, p. 243;Frame & Brachotte, 2015, p. 282; see Jungherr, 2016 for an overview). Furthermore, these studies have also found that there is still some interaction taking place (Frame & Brachotte, 2015;Tromble, 2016a), especially in the early days of Twitter (Graham, Jackson, & Broersma, 2016, p. 774) and especially when the incoming @-mentions are positive and when the MP's party is not populist (Tromble, 2016a). Regarding the latter, we also show that the lower degree of interaction by MPs of populist parties still holds now Twitter is far more widespread then several elections ago (cf.…”
Section: Resultsmentioning
confidence: 96%
“…Politicians can get around the limits imposed by the gatekeeping of mainstream media and control their own messages, but the wide accessibility of tweets might in fact lead to a loss of control of meaning and interpretation. In a qualitative study on the use of Twitter as a PR tool by MPs in France (Frame and Brachotte, 2015: 281), one politician interviewed remarked on the ‘interactive potential’ of Twitter, as well as its usefulness in ‘short-circuiting the traditional press networks’. A study of politicians’ use of social media in Sweden and Norway found that in fact usage is quite low, with ‘underdog’ politicians more likely to use social media than those in elected positions (Larsson and Kalsnes, 2014), while a similar study in the Netherlands found that politicians tend to use the platform more to promote their individual profile rather than their party platforms (Vergeer and Hermans, 2013).…”
Section: Women In Politics Women Politicians and The Mediamentioning
confidence: 99%
“…Since Twitter has become widely used by politicians in many countries, much has been written about the different ways in which this tool is, can and should be exploited (Frame and Brachotte 2015;Jackson and Lilleker 2011;Larsson and Moe 2013;Parmelee and Bichard 2013). Many researchers have denounced a general tendency for politicians to try to reproduce one-to-many communication strategies, tweeting at their voters rather than seeking to 'interact' with them in what is often presented as a more appropriate 'web 2.0' style (Small 2010;Vergeer and Hermans 2013).…”
Section: Introductionmentioning
confidence: 99%